2022
DOI: 10.3389/fonc.2022.880077
|View full text |Cite
|
Sign up to set email alerts
|

FBXW7 and the Hallmarks of Cancer: Underlying Mechanisms and Prospective Strategies

Abstract: FBXW7, a member of the F-box protein family within the ubiquitin–proteasome system, performs an indispensable role in orchestrating cellular processes through ubiquitination and degradation of its substrates, such as c-MYC, mTOR, MCL-1, Notch, and cyclin E. Mainly functioning as a tumor suppressor, inactivation of FBXW7 induces the aberrations of its downstream pathway, resulting in the occurrence of diseases especially tumorigenesis. Here, we decipher the relationship between FBXW7 and the hallmarks of cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 229 publications
2
20
0
Order By: Relevance
“…Among these proteins, FBXW7 attracted the most attention ( Supplementary Figure S6C ). It is well known that FBXW7 serves as a tumor suppressor that promotes ubiquitination of a wide range of oncoproteins for proteasomal degradation, including mTOR ( 14 , 15 , 28 30 ). In line with this, our results also showed that FBXW7 overexpression significantly inhibited the proliferation and metastasis of HCC cells in vitro ( Supplementary Figure S7 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Among these proteins, FBXW7 attracted the most attention ( Supplementary Figure S6C ). It is well known that FBXW7 serves as a tumor suppressor that promotes ubiquitination of a wide range of oncoproteins for proteasomal degradation, including mTOR ( 14 , 15 , 28 30 ). In line with this, our results also showed that FBXW7 overexpression significantly inhibited the proliferation and metastasis of HCC cells in vitro ( Supplementary Figure S7 ).…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have shown that F-box proteins play indispensable roles in drug resistance ( 6 , 12 ). As the target protein of FBXO9, FBXW7 has been reported to increase chemosensitivity of HCC cells ( 14 , 31 ). Accordingly, we explored the effects of FBXO9 knockdown on the sensitivity of HCC cells to lenvatinib and sorafenib, the two first-line drugs for HCC therapy.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations